Regional variation in rural transition in India. Issue 1 (2nd January 2020) - Bajar, Sumedha
ABSTRACT: The dramatic decline in the share of agriculture in India's gross domestic product from 52 percent in 1950–1951 to less than 17 percent in 2017–2018 necessarily implies a decline in the amount of labor this sector can employ. However, agriculture continues to be the largest employer in the country. Even when workers move out of the agricultural sector, they do not always leave rural areas. The movement from an agrarian economy to a non-agrarian one in India has not been matched by the expected shift from rural areas to urban areas. The macro scenario facing the country is that of low agricultural productivity, slow urbanization rates, and huge surplus labor in rural areas. But within this overall national picture, are there variations in terms of movement of labor away from agriculture? Are there more than one rural transition patterns being observed in the country? Are there contiguous areas in the country with a specific transition pattern which is common for a region? To answer these questions, this paper first takes a closer look at different types of transitions observed in the country. It then goes on to map the regions where workers have moved into agriculture, moved out of agriculture but remain in rural areas, and left the rural areas altogether respectively, in addition to regions with a prominent place for marginal workers.